Dual roles of glutathione in silver nanoparticle detoxification and enhancement of nitrogen assimilation in soybean (Glycine max (L.) Merrill). Issue 7 (3rd June 2020) - Ma, Chuanxin; Liu, Hong; Chen, Guangcai; Zhao, Qing; Guo, Huiyuan; Minocha, Rakesh; Long, Stephanie; Tang, Yuanzhi; Saad, Emily M.; DeLaTorreRoche, Roberto; White, Jason C.; Xing, Baoshan; et al.
Abstract : Glutathione can alleviate the silver nanoparticle-induced phytotoxicity and enhance the nitrogen assimilation in soybean. Abstract : Widespread use of silver nanoparticles (Ag NPs) as pesticides and fungicides in agriculture is a major environmental concern. In the present study, soybean ( Glycine max L.) was grown in Ag NP (0–62.5 mg kg −1 )-amended soil with or without the addition of glutathione (GSH). Ag NPs exerted severe phytotoxicity and caused the reduction of shoot and root biomass and total number of nodules or completely inhibited nodule formation at doses above 31.25 mg kg −1 . Synchrotron-based techniques were applied to analyze Ag speciation in both the soil and the soybean root tissues at harvest. The results indicate that the majority of Ag remained in the form of Ag NPs and that 23% was present as Ag2 S in soil; in both root and nodule tissues, Ag–GSH was the main component (40.6–88%) other than Ag NPs (12–59.4%), highlighting the important role of GSH in alleviating the Ag NP-induced toxicity. The addition of 0.8 mM GSH not only significantly increased fresh biomass by 85% in the 62.5 mg kg −1 Ag NP treatment but also decreased Ag accumulation by 24.8–27% in soybean tissues. Although the addition of 0.8 mM GSH reduced the nodule number and weight as compared to the control, the total nitrogen content in soybean co-treated with Ag NP and GSH was more than 5-fold higher than that in the Ag NP alone treatments, suggesting that GSH may be utilized as a nitrogen source while simultaneously alleviating Ag NP toxicity. The shoot and root contents of thiol compounds (cysteine and gamma-glutamylcysteine) in the GSH treatments were several folds higher than that in the control and Ag NP alone treatments. Further, higher levels of essential amino acids, particularly alanine, glutamate, and glutamine which play important role in N assimilation in plants, in soybean across all the treatments further confirmed that GSH was utilized as a nitrogen source, resulting in enhanced soybean growth. Taken together, this study clearly demonstrated the negative impact of Ag NPs on soybean productivity and N fixation and highlights the protective role of GSH against Ag NP-induced toxicity. These findings have significant relevance for developing future strategies to minimize crop loss in marginal or contaminated soils, subsequently enhancing global food security.